Therapeutic Potential of Nano-Sustained-Release Factors for Bone Scaffolds - Haoran Jiang; Meng Zhang; Yang Qu; Bohan Xing; Bojiang Wang; Yanqun Liu; Peixun Zhang (Journal of Functional Biomaterials)
Research on nano-sustained-release factors for bone tissue scaffolds has significantly promoted the precision and efficiency of bone-defect repair by integrating biomaterials science, nanotechnology, and regenerative medicine. Current research focuses on developing multifunctional scaffold materials and intelligent controlled-release systems to optimize the spatiotemporal release characteristics of growth factors, drugs, and genes. Nano slow-release bone scaffolds integrate nano slow-release factors, which are loaded with growth factors, drugs, genes, etc., with bone scaffolds, which can significantly improve the efficiency of bone repair. In addition, these drug-loading systems have also been extended to the fields of anti-infection and anti-tumor. However, the problem of heterotopic ossification caused by high doses has led to a shift in research towards a low-dose multi-factor synergistic strategy. Multiple Phase II clinical trials are currently ongoing, evaluating the efficacy and safety of nano-hydroxyapatite scaffolds. Despite significant progress, this field still faces a series of challenges: the immunity risks of the long-term retention of nanomaterials, the precise matching of multi-factor release kinetics, and the limitations of the large-scale production of personalized scaffolds. Future development directions in this area include the development of responsive sustained-release systems, biomimetic sequential release design, the more precise regeneration of injury sites through a combination of gene-editing technology and self-assembled nanomaterials, and precise drug loading and sustained release through microfluidic and bioprinting technologies to reduce the manufacturing cost of bone scaffolds. The progress of these bone scaffolds has gradually changed bone repair from morphology-matched filling regeneration to functional recovery, making the clinical transformation of bone scaffolds safer and more universal.